MAKNA SIMBOLIK DAN FUNGSI ULOS MASYARAT BATAK TOBA KABUPATEN SAMOSIR - Rodearni S Rodearni S; Ridwan Melay; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Culture is the expression of human ideas, ideas and actions in meeting the needs of everyday life, which is obtained through the process of learning and teaching. The culture conceptually has seven (7) components: Religion, Science, Technology, Economics, Social Organization, Language and Communication and Art. One of the artworks of the Batak Toba ethnic community is